How Do Institutional Frameworks Shape Financial Development in Developing Countries? - NAKHLI, MOHAMED SAHBI; GAIES, BRAHIM; GUESMI, KHALED; MOISSERON, JEAN-YVES (Bankers, Markets & Investors, 2020)
While the economic effects of financial development have been widely studied, less attention has been paid to the sources of such development, particularly in developing countries. Existing studies that have identified institutions as a driver of financial development have not taken into account the different institutional frameworks, such as democracy, political stability and social policies in Africa, where institutional and financial development is a challenge to trigger the economic take-off of countries. This paper aims to fill this gap by studying the effect of different institutional frameworks on financial development in a sample of North and sub-Saharan African countries using a panel ARDL analysis. In contrast to previous literature that supports a positive effect between institutions and finance, we find more nuanced results. While less corruption, expropriation, political instability and autocracy favor the financial sector, a higher level of social policies can undermine its development. These results validate the “hierarchy of institutions”-hypothesis and reveal a “social-financial” dilemma in African countries.